The impact of volatile economic conditions on corporate capital structure adjustment towards dynamic target in Pakistan - Sohail Amjed; S. M Amir Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
This paper aims to empirically investigate the impact of macroeconomic conditions such as banking sector performance, economic growth, inflation rate, interest rates and market capitalization on the adjustment speed towards dynamic capital structure targets in Pakistan for the period 1999 to 2013. The study also assesses the effect of adjustment speed on the financial performance of the firm. The annual adjustment speed of five industrial sectors was estimated separately by using a modified partial adjustment approach. The direction of causality between financial performance and annual capital structure adjustment speed was examined through the Granger causality test. The empirical results favor the presence of dynamic capital structure targets in Pakistan for all five industrial groups. We found that the capital structure adjustment speed significantly varies across industrial sectors and over time. The firms in Pakistan adjust their capital structure toward dynamic targets ranging from 23% to 46% annually depending on the country's macroeconomic conditions such as banking sector performance, economic growth, and interest rates. The deviation from the target capital structure also plays an important role in the capital structure adjustment speed. However, the empirical results fail to validate the effect of the inflation and market capitalization on the capital structure adjustment speed. The Granger causality test results show that a unidirectional causality runs from the capital structure adjustment speed to financial performance. The research finding may assist the non-financial corporate sector of Pakistan to structure an optimal mix of debt and equity capital to finance their operations and growth opportunities cost effectively. The study also provides insights that how to make adjustments in capital structure in response to changing economic conditions in order to reduce the financial cost of business. Scope of this study is limited to non-financial corporate sector of Pakistan.
Keywords: 330; dynamic leverage targets; capital structure adjustment speed; partial adjustment model; macroeconomic conditions